Prognostic impact of homocysteine levels and homocysteine thiolactonase activity on long-term clinical outcomes in patients undergoing percutaneous coronary intervention. Issue 6 (June 2017) - Hassan, Ahmed; Dohi, Tomotaka; Miyauchi, Katsumi; Ogita, Manabu; Kurano, Makoto; Ohkawa, Ryunosuke; Nakamura, Kazuhiro; Tamura, Hiroshi; Isoda, Kikuo; Okazaki, Shinya; Yatomi, Yutaka; Daida, Hiroyuki
Abstract: Background: Numerous studies have reported the relationship between elevated homocysteine (Hcy) levels and the risk of coronary artery disease. However, there is insufficient information about the effects of Hcy levels on long-term clinical outcomes in patients with coronary artery disease undergoing percutaneous coronary intervention (PCI). Methods: In the Juntendo-registry cohort from 2003 to 2004, pre-procedural Hcy levels and Hcy thiolactonase activity (HTlase) were measured in 315 consecutive all-comer patients who underwent PCI for stable coronary artery disease or acute coronary syndrome (ACS). Receiver-operating characteristic (ROC) curves were created to assess the optimal cut-off values of Hcy and HTlase. Multivariable Cox proportional hazard regression analysis was used to identify the predictors of clinical outcome. The primary endpoint was all-cause mortality. Results: The patients' mean age was 66 ± 9 years, and 82.5% were males. The median follow-up period was 10.5 years, and overall mortality was 24.5% (73 deaths). On ROC analysis, the optimal cut-off values of Hcy and HTlase were 13.5 μmol/L and 230 IU/L, respectively. Kaplan–Meier survival analysis showed associations of both higher Hcy levels and lower HTlase activity with worse prognosis (both log-rank p  < 0.001). On multivariate Cox proportional hazard regression analysis, higher Hcy was strongly associated with the primary outcome, and the adjusted hazard ratio was 3.3 (95% confidence interval, 1.8–5.6; p  < 0.001). Conclusions: Pre-procedural high Hcy levels and low HTlase activity were associated with worse long-term mortality in Japanese patients undergoing PCI. Moreover, Hcy levels are strongly predictive for mortality, independent of traditional risk factors. This may have implications for risk stratification and the therapeutic approach in this PCI era.